REPRESENTASI MASKULINITAS DALAM IKLAN “BOYS DON’T CRY” WHITE RIBBON - Ajeng Nur Fauziah; Stara Asrita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
This rigid construction of gender roles causes a bad influence on a man which can then turn into toxic masculinity. Many organizations in the world have carried out a movement to defend the issue of gender equality, one of which is the movement carried out by the White Ribbon in defending healthy masculinity. This study uses a qualitative method with a descriptive approach. The analytical technique used is Fairclough's critical discourse analysis, collecting data by observation by observing the video campaign